Peran Budaya Masyarakat Islam Jawa terhadap Kerukunan Umat Beragama - Huda, Dimyati (Prodi Sosiologi Agama, 2017)
Look at the fact that the conflict is still going on and the need for handling conflicts, especially religious conflicts with a way to enhance the religious harmony that lives on Earth in Indonesia with diverse cultures and beliefs. With a strategy for how to let religious unity could increase and coexist as expected of mankind. This research will be done in Blitar Regency, why so? In addition to the restriction of the problem, in the County, there is a majority religion of Islam which is closely linked to the traditions of Java in Keseharianya and Terdapat variants of religion and places of worship that looks very harmonious. The purpose of this research is to mendiskripsikan the findings of the role of popular culture in Islamic religious unity against Java. The results of this research are to boost religious harmony Lo needs an understanding of the functional theory of the latter is that humans have a sense of berdayaan because of the very limited human presence, ability, time, and power will be limited by the ability of mankind in control and affect the condition of the desire of her life. To realize religious harmony it is necessary policy leadership in favor of the people